Relations between Egypt and Mesopotamia from Prehistoric Times to the End of the Middle Kingdom. II. From the Protodynastic Period to the End of the Middle Kingdom. III. Conclusions - Ward, William A.
134-135: Appendix: The Piriform Mace-Head in Western Asia.